Flood Modelling of Premulung River, Bengawan Solo - Pangestu, Ferdi; Kuntoro, Arno Adi; Irianto, Eko Winar (Journal of Applied Agricultural Science and Technology, 2024)
Premulung River or commonly known as Kali Premulung is one of many branches of Bengawan Solo River in its upstream area. This river pass through one of the most historical cities in Central Java, Surakarta. The overcapacity of this river leads to flood event that has a negative impact on humans. The purpose of this research is to analyze the Premulung River capacity and simulate the flood caused by rainfall design. The hydrological matter was analyzed using Hydrognomon and HEC-HMS while flood modelling was analyzed using HEC-RAS software one- and two-dimension (1D & 2D) simulation. Model calibrations were carried out based on historical flood events (depth, duration, and area of inundation) and local interview due to data limitation. Based on the simulation, the flood modelling shows that the current capacity of Premulung River cannot accommodate its peak discharge for two (Q2) and twenty years (Q20) return period flood. There are two main spots identified flooded due to Q2 flood with depth varies from 40 to 80 cm and duration from 4 hour to 7 hour. For Q20 flood, there are also two same spots identified flooded with depth varies from 1.2 m to 1.8 m and duration from 6 hour to 9 hour. The result of this study can be a reference for flood dike design in the future which still require further detailed investigation.